Structural optimization of impregnated test cathodes - Duan, Shihao; Zhou, Xiaoyu; Song, Ruitong; Wang, Chenning; Xu, Zhenrui; Fu, Hao (Applied thermal engineering, 2025)
As the core component of vacuum electron devices, the cathode’s performance directly determines the working efficiency of the devices. However, traditional cathodes generally suffer from issues such as high heating power yet low temperature, long thermal equilibrium time, prolonged startup time, low heating efficiency, and significant deformation. To achieve the working temperature, a high heating power must be applied to the filament, leading to structural deformation, reduced lifespan, and instability in thermionic emission. To address these issues, this paper designs a novel cathode structure using ANSYS WORKBENCH. By shortening the support cylinder and emitter lengths, and introducing a bottom thermal shield and dual external thermal shields, the cathode’s performance is significantly enhanced. Experiments and simulations show that, at a heating power of 7.32 W, the emitter temperature of the new cathode increased by 32.92% compared to the original cathode, the thermal equilibrium time was reduced by 74.63%, startup time was shortened by 75.37%, heating efficiency was improved by 17.92%, and thermal deformation was reduced by 77.06%. Moreover, the minimum heating power required to reach the working temperature decreased by 51.37%. Additionally, the new cathode structure’s fundamental frequency was found to be 2353.6 Hz, well above the random vibration frequency range, effectively avoiding destructive resonance. These findings provide theoretical and technical support for the optimization of cathode designs. [Display omitted] •Innovative thermal shielding design.•Significant efficiency and reliability improvements.•Enhanced structural stability and resonance resistance.